Pakistan : Fourth and Fifth Reviews Under the Extended Arrangement and Request for Waivers of Nonobservance of Performance Criteria. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2014)
A 36 month, SDR 4,393 million (425 percent of quota) Extended Arrangement under the EFF was approved by the Executive Board on September 4, 2013 and the third review was completed on June 27, 2014, with a total of SDR 1,440 million disbursed. Fifth and sixth tranches totaling of SDR 720 million will be available upon the completion of this review.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet